(untitled) (Nigerian Journal of Physiological Sciences, 2022)
The parasympathetic vagus nerve supplies the heart and lung. The Parasympathetic activity modifies the heart rate and force of contraction in the heart and Airway bronchial smooth muscle constriction and hypersecretion of mucus in the lungs. There is a link between these two components. Hence this study is designed to find the association between Spectral analysis of heart rate variability and pulmonary function tests in bronchial asthma patients. In this study, 30 asthmatic patients were recruited from the respiratory medicine outpatient department and 30 healthy volunteers were included. Pulmonary function tests and heart rate variability was recorded in the physiology department. The pulmonary function parameters were found significantly reduced in the asthmatic patient and it shows obstructive lung diseases. Heart rate variability parameters were found a statistically significantly decreased mean HR, VLF ms2, and LF ms2 in the asthmatic patients when compared to controls. HF ms2 was found significantly increased in the asthmatic patient. These HF ms2 were increased to represent parasympathetic hyperactivity. This study concluded there is parasympathetic dominance in asthmatic patients. The parasympathetic activity might be one of the reasons for increases the airway bronchoconstriction and hypersecretion of mucus. There is a negative correlation was found between FEV1 value and HF ms2. A decrease in the FEV1 value leads to an increase in HF ms2.